Antioxidant Activity, Physical and Organoleptic Test of Tapai Pisang Kepok Ice Cream - Syafii, Firdaus (Program Studi Teknologi Hasil Pertanian, Politeknik Gorontalo, 2024)
The aimed of this study was to determine the effect of adding tapai banana kepok on antioxidant activity, physical and organoleptic properties of ice cream. The method used in this study was a complete randomized design (RAL). The factors used in this study were the concentration of tapai banana kepok, which was 0%, 10%, 20%, 30%, and 50%. The measured responses were antioxidant activity, total solids analysis, melting time, overrun and hedonic tests on color, taste, aroma, texture, and overall attributes. Based on the results of the study showed that the addition of tapai banana kepok in making ice cream had a significant influence on the total solids value (p<0.05), melting speed (p<0.05), overrun (p<0.05), antioxidant activity (p<0.05) and hedonic tests on taste attributes (p<0.05), aroma (p<0.05), texture (p<0.05) and overall (p<0.05). The more the amount of banana tapai added to ice cream, the greater the total solids value (F4=45.27%), the longer melting time (22.05 minutes/100g), the smaller overrun (F4=22.45%), and the stronger antioxidant activity (F4=98 ppm). Based on the hedonic test, formula 2 (20% addition of banana tapai) gave the most preferred overall sensory attribute (F2 = 5.12). In addition, formula 2 has physical properties that are in accordance with the SNI ice cream quality requirements and has moderate antioxidant power